The feigenbaumes δ for a high dissipative bouncing ball model - Oliveira, Diego F. M. [UNESP]; Leonel, Edson D. [UNESP] (FapUNIFESP (SciELO), 2008)
We have studied a dissipative version of a one-dimensional Fermi accelerator model. The dynamics of the model is described in terms of a two-dimensional, nonlinear area-contracting map. The dissipation is introduced via inelastic collisions of the particle with the walls and we consider the dynamics in the regime of high dissipation. For such a regime, the model exhibits a route to chaos known as period doubling and we obtain a constant along the bifurcations so called the Feigenbaum's number 8.
Keywords: Bouncing ball model; Dissipation; Feigenbaum number; Lyapunov exponent